Does whole-body exercise affect respiratory muscle function? A study of various athletic populations. - Terblanche, E.; Kroff, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
There is no conclusive evidence that lung function and respiratory muscle (RM) function are affected by regular land-based exercise. It appears that swimmers possess greater lung volumes than predicted, yet results on respiratory muscle strength and endurance are discrepant. It is also known that significant morphological differences exist between competitive athletes and non-athletes. However, the same reference equations, which are primarily based on morphological characteristics, are used for athletic and non athletic populations to predict RM strength and endurance. The aim of this study was to compare the RM strength and endurance of various athletic populations and to establish whether current reference values are adequate to predict RM function in athletes. Methods: One hundred and sixty subjects (aged 18 to 30 years) from eight different sport codes participated in this study. All athletes were well-trained at the time of the study. Maximal inspiratory pressure (MIP) was measured as an indication of RM strength and maximal voluntary ventilation in 12 seconds (MVV) was measured as an index of RM endurance. Kinanthropometric variables, such as stature, body mass, and various circumferences and breadths were included in the assessments. Results: There were no significant differences in MIP, MEP or MVV between endurance and non-endurance athletes (MIP: 122 + 36 cmH2O vs 126 + 28 cm H2O; MVV: 168 + 34 L/min vs 186 + 32 L/min). Although swimmers had slightly higher MIP and MVV values than land-based athletes, the differences were not statistically significant. In all cases, athletes had superior respiratory muscle strength and endurance compared to age-matched sedentary controls. Multiple regression analyses revealed that gender, mesomorphy and exercise sessions per week predicted 35% (SEE = 26.6 cmH2O) of the variance in MIP, while gender, relative sitting height, FEV1 and PEFR predicted 78% (SEE = 18.2 L.min-1) of the variance in RM endurance (MVV). Discussion: This is the first study to show that there are little differences in the RM function of endurance and non-endurance athletes, but swimmers are likely to possess superior RM function compared to other athletes. However, evidence exist that whole-body training does affect RM function, provided that the exercise and training is of high intensity. Importantly, we developed reference equations that provide more suitable reference values for athletes than previously reported.